“Across-the-Top” Biportal Endoscopic Spinal Surgery for Right-Sided Pathologies: Technical Note - Ansari, Mohammad A.; Yusufi, Faiz K. (Asian Journal of Neurosurgery, 2025)
Unilateral biportal endoscopic (UBE) spine surgery has become a promising minimally invasive technique for treating lumbar spinal pathologies, offering advantages such as reduced blood loss, minimal tissue disruption, and faster recovery. The “across-the-top” technique, a contralateral decompression approach, effectively treats right-sided lumbar lesions while preserving midline stabilizing structures. This study evaluates this technique's surgical methodology, safety, and clinical outcomes in patients with exclusive right-sided spinal pathology.This prospective observational study included 24 patients presenting with exclusive right-sided lumbar spinal pathologies, such as ligamentum flavum hypertrophy or disc herniation with radiculopathy and/or numbness, who met the inclusion criteria. All patients underwent UBE decompression using the “across-the-top” technique after informed consent. Surgeries were performed under general anesthesia in the prone position, with the surgeon positioned on the patient's left side. Two right paramedian skin incisions were made to establish the endoscopic (cranial) and working (caudal) portals. Port docking was performed at the lower vertebral pedicle and 3 cm cranially, guided by C-arm fluoroscopy. Paraspinal muscle dissection and bony decompression were performed using an RF probe and high-speed drill. The ligamentum flavum was excised to expose neural elements, with decompression confirmed by visualization of the epidural space. Hemostasis was achieved, and a drain was placed before wound closure. All patients were followed for 3 months postoperatively to assess outcomes and complications.All surgeries were completed successfully without intraoperative complications. No patient experienced dural tears, nerve root injury, or infections. Only two patients had residual numbness at 3 months; all others had significant symptomatic relief. Most were discharged on postoperative day 2.The “across-the-top” UBE technique is a safe, effective, and ergonomic technique for right-sided lumbar pathology, providing excellent decompression while preserving stabilizing structures and ensuring rapid recovery.
Keywords: UBE; lumbar canal stenosis; decompression; minimally invasive surgery